2020
DOI: 10.3390/ijerph18010264
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Functional Fitness Test Performance and Abdominal Obesity in Healthy Elderly People: Results from the National Physical Fitness Examination Survey in Taiwan

Abstract: The relationships between different functional fitness performance and abdominal obesity among the elderly have not been widely discussed in the literature. The present study aimed to investigate the associations between functional fitness test performance and abdominal obesity in Taiwanese elderly people. A total of 22,399 items of data from the National Physical Fitness Survey Databases in Taiwan (NPFSD 2014-15) were reviewed and analyzed. The quartiles of functional fitness test results were identified as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…We reviewed data derived from the National Physical Fitness Survey Databases in Taiwan (NPFSD 2014–15) from Taiwan’s Sports Administration, a branch of the Ministry of Education. All participants were recruited using convenience sampling from 35 examination stations in 20 cities or counties in Taiwan; the detailed procedure has been described elsewhere [ 13 15 ]. Participants completed a questionnaire on their demographic characteristics and life habits, and we measured resting heart rate and blood pressure for safe preliminary screening before conducting physical fitness measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed data derived from the National Physical Fitness Survey Databases in Taiwan (NPFSD 2014–15) from Taiwan’s Sports Administration, a branch of the Ministry of Education. All participants were recruited using convenience sampling from 35 examination stations in 20 cities or counties in Taiwan; the detailed procedure has been described elsewhere [ 13 15 ]. Participants completed a questionnaire on their demographic characteristics and life habits, and we measured resting heart rate and blood pressure for safe preliminary screening before conducting physical fitness measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Self-reported health status and obtained from the following questionnaire item: “In general, would you say your health is excellent, good, fair, poor, or very poor?” In this analysis, we have combined the responses into a ternary outcome, where self-reported health status could be health status (a response of “excellent” or “good”), fair (a response of “fair”), or unhealthy status (a response of “poor” or “very poor”), in order to concentrate the categories for further comparisons. This approach has been presented in the previous studies [ 13 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, one person may have good levels of flexibility in the glenohumeral joint but not in the acetabulofemoral joint [ 39 ]. Likewise, since of all the anthropometric and health variables analyzed, only S&R correlated with AG—and despite some studies have verified that subjects with a higher percentage of fatty tissue present lower levels of flexibility [ 41 , 42 ]—it cannot be ruled out that this result is due to the presence of central adiposity, which may limit trunk flexion, and therefore, S&R results [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result aligns with the findings of Giuriato et al (2021) [ 54 ] since they verified that the greater HE and the lower WHR, the better the results obtained in SLJ by adolescents. Moreover, Singh Sidhu (2018) [ 51 ] points out that although HE conditions SLJ marks, further aspects also determine SLJ results, such as muscular strength and power, jumping technique, lower extremity length, BMI, and biomechanical factors [ 44 ]. For this reason, it is conceivable that in some studies (including the present research), only weak correlations between HE and SLJ are found.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed data derived from the National Physical Fitness Survey Databases in Taiwan (NPFSD 2014-15) from Taiwan's Sports Administration, a branch of the Ministry of Education. All participants were recruited using convenience sampling from 35 examination stations in 20 cities or counties in Taiwan; the detailed procedure has been described elsewhere [9][10][11]. Participants completed a questionnaire on their demographic characteristics and life habits, and we measured resting heart rate and blood pressure for safe preliminary screening before conducting physical tness tests.…”
Section: Study Design and Participantsmentioning
confidence: 99%